THE CONSTRUCTION OF INDONESIAN EFL LEARNERS’ IDENTITIES: A NARRATIVE-BASED CASE STUDY - Abdusyukur, Muhammad Rafi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The identity that the learners construct during the English learning process is essential to understand how the EFL learners continuously negotiate the identities they have until they successfully achieve adequate proficiency in English. This narrative-based case study investigates how the learning of English has constructed the learner identity of two Indonesian postgraduate students who graduated from the English Education Department. Categorized under narrative inquiry design, this research explored the participants’ personal narratives related to their experiences during the English language learning process. In the early phase of identity construction, both participants showed little or no relevance in learning English because it was imposed on them through the school curriculum. However, soon they developed positive identities which later turned to be false positivity. Thus, these distressing moments asked for more investments from the participants. This study successfully confirms the notion of complex, multilayered, and multifaceted proved by the narratives that emerged from the participants' lived English learning experiences.